2013
DOI: 10.1002/app.39778
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive behavior of graphene nanoplatelets/carbon black/silicone rubber nanocomposite

Abstract: Silicon rubber (SR) filled with carbon black (CB) and carbon black (CB)/graphene nanoplatelets (GNPs) hybrid fillers are synthesized via a liquid mixing method. The effects of filler type on the electrical properties and piezoresistive properties (near the region of the percolation) of the conductive SR composites are studied. It is suggested that the conductivity of the composite filled with CB/GNPs hybrid fillers in the mass ratio of 2 : 4 is much higher than that in other ratio. Percolation threshold for CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…3 Because GNPs has 2-D plane structures and large surface area, the large surface van der Waals force of GNPs particle-particle will result in GNPs reunion. 26 For geometrical considerations, graphene layers are easier to structure in a triangle framework, which established a stable conducting network.…”
Section: B Stability At Constant Temperaturesmentioning
confidence: 99%
“…3 Because GNPs has 2-D plane structures and large surface area, the large surface van der Waals force of GNPs particle-particle will result in GNPs reunion. 26 For geometrical considerations, graphene layers are easier to structure in a triangle framework, which established a stable conducting network.…”
Section: B Stability At Constant Temperaturesmentioning
confidence: 99%
“…Especially, flexible pressure sensors with high sensitivity in low deformability (strain) are highly desirable for better emulating human skin and more precisely capturing human motions . Piezoresistive‐type sensor, based on the change in the resistance of materials with mechanical deformation, is a promising pressure sensor due to its simple fabrication, low cost, and easy signal collection . Conventionally, flexible and stretchable rubbers filled with conductive carbon such as carbon black, carbon nanotubes, and graphene, are used as sensing materials for piezoresistive sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have recently demonstrated that polymers especially soft elastomers incorporated with these conducting fillers could show significant piezoresistive performance [8]. A low cost technique was introduced in this study to carry out most of the required measurements in order to characterize the electro-mechanical properties of QTC using both DC and AC applied voltage.…”
Section: Discussionmentioning
confidence: 99%